Dawnrunner - V, Ram (Dark Horse Books, 2024)
"A century ago, a portal opened over Central America and giant monsters known as the Tetza came through, changing everything we knew. Now the world bends all its effort to build the Iron Kings--great mechs driven by pilots--that battle the Tetza in gladiatorial combat for humanity's continued survival. War has turned to sport. Star jockey Anita Marr has been chosen to pilot a secret new prototype that could change the tide in humanity's favor. After a difficult first battle together, Anita begins to uncover and understand the unusual connection forming between herself and the experimental new Iron King, Dawnrunner. As the Tetza threat grows, Anita, Dawnrunner, and their secrets will become mankind's last hope. Are we doomed or will dramatic revelations push Anita and Dawnrunner to transcend into something new?"--